Knowledge-based entrepreneurship in Romania - Radu Gheorghiu; Gemina Turlea; Stela Andrei; Romana Emilia Cucuruzan (Center for Social and Economic Research (CASE), 2010)
The importance of new firm creation in the post-Communist economies of East Central Europe (ECE) has been subject to extensive research. This paper focuses on an area of entrepreneurship which has received relatively little attention in the transition economy context but which is of particular importance for the modernization of the transitioneconomies: knowledge-based entrepreneurship (KBE), or new firm creation in industries considered to be science-based or to use research and development (R&D) intensively. We begin by sketching the situation in Romania's small and medium-sized business sector, then proceed to study the conditions for high-tech firm development in the country, focusing on the institutional infrastructure and policy initiatives. We then turn to the analysis of a series of case studies of firms active in the areas of information technology, pharmaceuticals, and advanced chemistry. Among the issues treated are the resources and strategies involved in KBE in Romania, the relationships (networks) of the firms in question and how they are used for knowledge acquisition. We find that overall Romania appears to be a poor location for KBE, with R&D spending as a percentage of GDP very low (and falling for much of the transition period) and a poorly educated population. Most of the firms studied here rely on foreign markets for development of their more innovative products, whereas domestic markets provide opportunities for higher volume sales of less advanced products. The nature of strategic business relationships and networks varies significantly across the firms studied, with some engaging in virtually no collaboration in the area of innovation, and others engaging quite intensively with academic partners in product development.
Keywords: L26; O31; O52; P27; 330; Knowledge-based economy; entrepreneurship; transition; post-communist; SMEs; Romaina; Wissensgesellschaft; Innovation; Forschung; Informationstechnik; Entrepreneurship-Ansatz; KMU; Hochtechnologie; Systemtransformation; Rumänien